CMV (cytomegalovirus) infection in infant with leukocytosis without symptoms: A Case Report : A Case Report of CMV - Hosseinpouri, Arghavan (Archives of Advances in Biosciences, 2021)
Introduction: CMV is an infectious disease usually transfer from pregnant women to the fetus, or during breastfeeding transfer to the infant and have signs and symptoms like losing weight at birth, leukocytosis, diarrhea. Case presentation: In this case, the one year old girl does not has any sign and symptoms except leukocytosis and the infant mothers does not has any disease during pregnancy. The experiments were prescribed for diagnosing the reason of leukocytosis were CBC, Urine analysis, Immunoassay tests for EBV and CMV and serologic tests for Covid19, wright and Widal agglutination and 2ME tests for Brucella. Conclusions: The results showed the rate of IgM and IgG Antibody were 27.688 and 228.761 respectively. It is noteworthy that there were no other signs and symptoms in this baby, which are commonly described for CMV infection, and other tests have been reported as usual.